Flashbulb Memory and its Relationship with The probabilistic Approach - Aziz Abbas, Riadh (Al-Adab Journal, 2021)
The present Research aims at knowing the following; the flashbulb memory among the research sample. the probabilistic Approach among the research sample. correlation Between flashbulb memory and the probabilistic Approach among the research sample. In sample of the test consists of (180) university Lecturers. Where males are (90). females are (90). the order to achieve the objectives of this research the has constructed two scales The first is used for measuring the flashbulb memory and the second for measuring the probabilistic Approach. The Research Reached the following results: The university Lecturers characterizes with the flashbulb Memory. the university Lecturers used weakly the probabilistic approach. there is an inverse Relationship between the flashbulb Memory and the probabilistic Approach. Finally in the light of Results the Research has arrived at a number of Recommendations and suggestions.